Shahryar Nashat - keep begging - Castets, Simon 1984-; McLean-Ferris, Laura 1982- (Swiss Institute, 2021)
"Bodies function, fight, and fail. People bear witness to these processes every day, actively and passively, in the flesh and on-screen. But bodies are also unruly: they desire and shapeshift and betray. This oscillation between the realities of mortal progression and everything that transpires in those indeterminate zones serves as the basis for Swiss artist Shahryar Nashat's visceral, future-facing practice. What Nashat presents to us, the viewer, are depictions of humanness, of aliveness, filtered through ways of seeing that may have not yet arrived. There are hypotheticals at play, although the sensations generated in Nashat's sculptures and videos point toward primal expressions of desire and survival."--Provided by publisher
Impressum: Published for the exhibitions "Shahryar Nashat: The Cold Horizontals" at Kunsthalle Basel, September 29, 2017-January 7, 2018, and "Shahryar Nashat" at Swiss Institute, New York, March 20-June 2, 2018
Keywords: Nashat, Shahryar -- 1975-; Nashat, Shahryar / 1975- / Exhibitions; Nashat, Shahryar / 1975-; Exhibition catalogs; Bildband; Ausstellungskatalog -- Kunsthalle Basel -- 29.09.2017-07.01.2018 -- Basel; Ausstellungskatalog -- Swiss Institute -- 20.03.2018-02.06.2018 -- New York, NY